Appreciating literature (Glencoe/McGraw-Hill, 1991)
This book gives you both great literature to think about and an organized way to think about it. After each selection, you will find three kinds of Study Questions. These questions will focus your thoughts on recalling the detail of the selection, interpreting the meaning of those details, and extending the meaning of those details into your own experience. Special feature sections will help you think about a witer's vocabulary, a particular literary element, and what you do when you yourself write about literature.